Pengaruh Variasi Persentase Cangkang Kerang (Caco3) Dan Karbon Arang Kayu Nani Pada Proses Karburasi Terhadap Sifat Mekanis Serta Laju Korosi Baja Karbon Sedang - Graciadiana I Huka; Josef Matheus; R.R. Lekatompessy; Nevada J.M Nanulaitta (Jurusan Teknik Mesin, 2025)
The effect of additives such as seashells (containing CaCO₃) and nani wood charcoal on the mechanical properties of steel during the carburizing process is significant. The addition of CaCO₃ acts as a catalyst, accelerating carbon diffusion into the steel's microstructure, thereby increasing surface hardness and flexural strength. The results showed that increasing the percentage of CaCO₃ up to a certain point can increase the hardness and strength of the steel, with the highest hardness value achieved at a variation of 50% CaCO₃ and 50% nani wood charcoal, at approximately 21.93 HRC. Hardness testing showed that the variation of additives directly affected the final hardness, with the highest value being achieved at the optimal combination of CaCO₃ and nani wood charcoal. In addition to hardness, other mechanical properties, such as bending strength, also showed an increasing trend with increasing CaCO₃ proportions up to the optimal point, namely at a variation of 70% CaCO₃ and 30% nani wood charcoal, which resulted in a bending stress of 32.64 MPa and a bending strength of 3336.14 MPa. Therefore, the adjustment of the proportion of additives is a key factor in optimizing the mechanical properties of steel through the carburizing process enriched with these natural materials. Keywords: seashells, nani wood charcoal, catalyst, a bending strength